2015
DOI: 10.3390/nu7032026
|View full text |Cite|
|
Sign up to set email alerts
|

Interpreting the Australian Dietary Guideline to “Limit” into Practical and Personalised Advice

Abstract: Food-based dietary guidelines shift the focus from single nutrients to whole diet. Guideline 3 of the Australian Dietary Guidelines (ADG) recommends “limiting” discretionary foods and beverages (DF)—Those high in saturated fat, added sugars, salt, and/or alcohol. In Australia, DF contribute 35% of total energy intake. Using the ADG supporting documents, the aim of this study was to develop a food‑based educational toolkit to help translate guideline 3 and interpret portion size. The methodology used to produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Discussion about assessment of knowledge of nutrients versus whole foods was evident across all focus groups. Although there has been a recent emphasis on considering foods rather than nutrients in making recommendations [ 34 ], some participants still indicated that testing the nutrient knowledge of Australian adults would be important to include in a tool assessing nutrition literacy. Participants identified specific nutrients (such as salt, fat, and fibre) in their discussion within this theme as examples.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Discussion about assessment of knowledge of nutrients versus whole foods was evident across all focus groups. Although there has been a recent emphasis on considering foods rather than nutrients in making recommendations [ 34 ], some participants still indicated that testing the nutrient knowledge of Australian adults would be important to include in a tool assessing nutrition literacy. Participants identified specific nutrients (such as salt, fat, and fibre) in their discussion within this theme as examples.…”
Section: Resultsmentioning
confidence: 99%
“…Although there is a large body of research that focuses on the effects of isolated nutrients on health and disease, there is increasing recognition of the biological complexity of foods and health [ 35 ], and of the benefits of addressing eating patterns and dietary quality. In fact, there has been a recent shift away from nutrient-based recommendations to considering whole foods in the context of dietary patterns [ 34 ]. The latest release of the ADG makes recommendations based on whole foods on the premise that most people following the guidelines would meet nutrient recommendations and that advice on single nutrients is difficult to apply [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…It would be advisable to reduce the sodium content in discretionary foods, as well as to reduce the intake of these foods to more occasional consumption and in smaller portions. These foods should only be consumed in addition to core foods, depending on age, gender, sex, height, physical activity level, and the presence of excess weight [44].…”
Section: Discussionmentioning
confidence: 99%
“…Occasionally consumed food servings could be included instead of other basic groups in terms of macronutrient content, but if professionals add them as “extra foods”, high caloric diets could be reached. In Australia, a food tool-kit was developed to calculate the maximum number of occasionally consumed food servings that could be included in a diet as extra energy in active individuals, but not in the low-calorie pattern [11]. To the author´s knowledge, this is the first tool to present the combination of portions of frequently consumed foods to fit each portion of occasionally consumed foods, in order to adjust macronutrient intakes and to allow for the consumption by anyone (different caloric intakes).…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have shown a positive association between consumption of these foods and non-communicable diseases [9,10], they are regularly eaten and can contribute to the overall enjoyment of eating, often in the context of social activities and family or cultural celebrations [11]. Spanish diets are characterized by an inclination toward meat products [12]; Central and Northern European countries show a preference for red meats [13].…”
Section: Introductionmentioning
confidence: 99%